Enhanced Raman Scattering of CuPc Films on Imperfect WSe2 Monolayer Correlated to Exciton and Charge‐Transfer Resonances. (31st October 2018) - Liu, Yanran; Gao, Zhibin; Chen, Ming; Tan, Yang; Chen, Feng
Abstract: Recently, 2D transition‐metal dichalcogenides (2D TMDCs) are identified as ideal substrates for surface‐enhanced Raman scattering (SERS). However, the effect of enhancement factor (EF) on TMDCs is lower than metal‐based SERS substrates. Here, it is demonstrated that the SERS performance of WSe2 monolayer can be enhanced via tailoring the atomic ratio of WSe2 ; this correlates to the exciton and charge‐transfer resonances. CuPc molecules are adsorbed onto WSe2 monolayers as the probe molecules, and the atomic ratio (Se:W) of WSe2 is tailored from 2 to 1.92. For an atomic ratio of 1.96, the maximum EF on irradiated WSe2 is more than 120; this is enhanced by more than 40 times compared with pristine WSe2 . The amplitude of exciton and charge‐transfer resonances is estimated by femtosecond optical pump‐probe measurement and a bipolar junction transistor (BJT) consisting of CuPc film and 2D materials. It is found that the intensity of resonances in the CuPc–WSe2 system is tailored by the atomic ratio of WSe2 . This is closely correlated to the SERS performance of WSe2 . This study shows that the SERS performance of WSe2 is enhanced by tuning the atomic ratio of WSe2 and provides qualitative theoretical explanations for the mechanism of enhanced SERS. Abstract : Here, it is demonstrated that the surface‐enhanced Raman scattering performance of the WSe2 monolayer can be enhanced via tailoring the atomic ratio of WSe2, which is correlated to the exciton and charge‐transfer resonances. The amplitude of the exciton and charge‐transfer resonances is estimated by the femtosecond optical pump‐probe measurement and a bipolar junction transistor consisting of the probe molecules and WSe2 .